Financial and legal regulation of blockchane technology: status and prospects of cryptovolute use - Tipanov, Vladyslav; Drachov, Oleksii; Tkalenko, Svitlana; Mirzodaeva, Tetiana; Syerova, Lyidmila (My University, 2021)
Розглянуто сутність криптовалют та запропоновано визначення їх правового статусу. Вивчено досвід деяких юрисдикцій щодо можливостей і загроз використання та регулювання криптовалют. Автори проаналізували ринок криптовалют. Фактори, що призвели до широкого використання криптовалюти, включають фінансову нестабільність, значні валютні коливання, обмеження потоків капіталу та інфляцію валюти в країні. Розглянуто проблему захисту інформації з використанням технології блокчейн, яка вирішується поєднанням блокового проектування та криптографічного захисту.

The essence of cryptocurrencies is considered and the definition of their legal status is offered. The experience of some jurisdictions regarding the opportunities and threats of using and regulating cryptocurrencies has been studied. The authors analyzed the cryptocurrency market. The factors that led to the widespread use of cryptocurrency, which include financial instability, significant currency fluctuations, limiting capital flows and inflation of the currency in the country. The problem of information protection using blockchain technology, which is solved by a combination of block design and cryptographic protection, is considered.
Keywords: технологія блокчейн; криптовалюта; віртуальна валюта; правове регулювання криптовалют; функції держави; оподаткування криптовалют; technology blockchain; cryptocurrency; virtual currency; legal regulation of cryptocurrencies; state functions; cryptocurrencies taxation; кафедра туристичного та готельного бізнесу